Pengaruh Reputasi Kantor Akuntan Publik, Keberadaan Komite Audit, dan Prior Opinion Terhadap Pemberian Opini Audit Going Concern pada Perusahaan Manufaktur di Bursa Efek Indonesia - I Gusti Ayu Agung Omika Dewi; Ni Made Niki Premashanti (Universitas Matana, 2020)
Going Concern audit opinion are opinion was published by auditor to give due consideration about the ability of entity to hold on the business for the next year. The purpose of this study is to determine and analysis (1) The effect of The Public Accounting Firm’s Reputation against the giving of going concern audit opinion, (2) The effect of Existence Audit Committee against the giving of going concern audit opinion, and (3) The effect of Prior Opinion against the giving of going concern audit opinion. The sample were obtained using purposive sampling method. Sample in this study only 52 companies over five years with 260 observation data. The data analysis technice which is used in the research is logistic regression. The result of this research show (1) The Public Accounting Firm’s reputation have positive effect to the giving of going concern audit opinion, (2) The Existence Audit Committee have negative effect to the giving of going concern audit opinion, and (3) The Prior Opinion have positive effect to the giving of going concern audit opinion.